2019
DOI: 10.1038/s41598-019-53508-4
|View full text |Cite
|
Sign up to set email alerts
|

SMN complex member Gemin3 self-interacts and has a functional relationship with ALS-linked proteins TDP-43, FUS and Sod1

Abstract: The predominant motor neuron disease in infants and adults is spinal muscular atrophy (SMA) and amyotrophic lateral sclerosis (ALS), respectively. SMA is caused by insufficient levels of the Survival Motor Neuron (SMN) protein, which operates as part of the multiprotein SMN complex that includes the DEAD-box RNA helicase Gemin3/DDX20/DP103. C9orf72, SOD1, TDP-43 and FUS are ranked as the four major genes causing familial ALS. Accumulating evidence has revealed a surprising molecular overlap between SMA and ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 129 publications
(168 reference statements)
0
12
0
Order By: Relevance
“…This is suggested by the altered binding of mutant HSPB8 (p.K141N and p.K141E) to the RNA helicase DDX20 [449]. This component of the SMN (survival of motor neuron) complex and snRNPs is involved in transcriptional regulation and RNA processing, with functional connections to proteins associated with motor neuron degeneration, such as TDP-43 [450,451]. Along the same lines, decreased TDP-43 expression and altered splicing of TDP-43 target genes was recently reported in a muscle samples from patient with HSPB8-related neuromyopathy [440].…”
Section: Rna Metabolismmentioning
confidence: 99%
“…This is suggested by the altered binding of mutant HSPB8 (p.K141N and p.K141E) to the RNA helicase DDX20 [449]. This component of the SMN (survival of motor neuron) complex and snRNPs is involved in transcriptional regulation and RNA processing, with functional connections to proteins associated with motor neuron degeneration, such as TDP-43 [450,451]. Along the same lines, decreased TDP-43 expression and altered splicing of TDP-43 target genes was recently reported in a muscle samples from patient with HSPB8-related neuromyopathy [440].…”
Section: Rna Metabolismmentioning
confidence: 99%
“…Moreover, this study identified that NCDN and SMN interact within mobile cytoplasmic granules [ 76 ]. Interestingly, FUS and SMN are shown to share a common pathway in the context of neurobiology and ALS [ 6 , 7 , 23 , 88 ]. FUS is found to associate with the SMN complex through a direct interaction with SMN [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…DDX20 is associated with a neurogenerative disease SMA ( Charroux et al, 1999 ). Functional loss of DDX20 was observed in ALS on disruption of high-risk gene FUS ( Cacciottolo et al, 2019 ) . In modules-4, TP53 interacting proteins are majorly enriched with mRNA splicing function and highly associated with neoplasms diseases.…”
Section: Discussionmentioning
confidence: 99%